1999
DOI: 10.1001/archopht.117.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Basal Linear Deposit and Large Drusen Are Specific for Early Age-Related Maculopathy

Abstract: To determine the distributions of basal laminar and basal linear deposits in Bruch membrane (BM) with respect to age and early age-related maculopathy (ARM). Methods: The foveas of 41 human eyes (Ͻ60 years [n = 9]; Ն60 years [n = 32]), preserved no later than 3.5 hours post mortem, were examined using light and electron microscopy. Ten eyes met histopathologic criteria of the Alabama Age-related Macular Degeneration Grading System for early ARM. We calculated the specificity, sensitivity, and odds ratios for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
261
3
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(274 citation statements)
references
References 55 publications
9
261
3
1
Order By: Relevance
“…21,22 We previously reported that mice chronically exposed to HQ developed sub-RPE deposits and BrM thickening consistent with changes in early stages of human AMD. 57 Here, we found that RPE from these mice showed increased levels of phosphorylated Hsp25. However, in contrast to ARPE-19 cells, our results indicate that Hsp25 mRNA and protein levels were dramatically decreased in mice chronically exposed to HQ.…”
Section: Hsp27 and Oxidative Stress In Rpe 1209mentioning
confidence: 60%
“…21,22 We previously reported that mice chronically exposed to HQ developed sub-RPE deposits and BrM thickening consistent with changes in early stages of human AMD. 57 Here, we found that RPE from these mice showed increased levels of phosphorylated Hsp25. However, in contrast to ARPE-19 cells, our results indicate that Hsp25 mRNA and protein levels were dramatically decreased in mice chronically exposed to HQ.…”
Section: Hsp27 and Oxidative Stress In Rpe 1209mentioning
confidence: 60%
“…Basal deposits are the strongest histopathological marker of aging and age-related disease (Sarks, 1976;Green and Enger, 1993;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999). The location and composition of these deposits distinguish aging from AMD.…”
Section: Discussionmentioning
confidence: 99%
“…The location and composition of these deposits distinguish aging from AMD. Basal laminar deposits (BlamD), which form between the RPE cell and basement membrane, are a normal aging change early, but become specific for AMD when they become thick and contain cellular debris, 'long spaced collagen', membranous structures, lipid, and inflammatory proteins (Sarks, 1976;Newsome et al, 1987;Green and Enger, 1993;van der Schaft et al, 1994;Spraul et al, 1996;Spraul and Grossniklaus, 1997;Curcio and Millican, 1999;Anderson and Ozaki, 2001;Johnson et al, 2002;Leu et al, 2002). The most sensitive and specific histopathologic marker of AMD is basal linear deposits (BlinD), which form in the inner collagenous layer of Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cholesterolaccumulating sublayer of BrM is an apparent precursor to basal linear deposit, thought to provide a cleavage plane for dissecting choroidal vessels. 9,45 Therefore, cholesterol may play a role in promoting mechanical instability in ARM as well as atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%